PENINGKATAN KUALITAS AIR BERSIH DI KAWASAN PERUMAHAN JALAN PADAT KARYA KELURAHAN UMBAN SARI KECAMATAN RUMBAI DENGAN METODE FILTRASI KARBON AKTIF - Vega Ervina Lase; Virgo Trisep Haris; Muthia Anggraini (Prokons: Jurnal Teknik Sipil, 2022)
AbstractWater is one of the basic human needs in meeting daily needs. Groundwater around the residential area on the labor-intensive road, Urban Sari sub-district, Rumbai sub-district has poor water conditions. This can be proven by the release of cloudy and rusty water. One of the water treatment efforts that can be done is by using a filtration process using activated carbon as a filtration material with the type of filtration media, namely single media. The purpose of this study was to determine the decrease in the parameters of turbidity, pH, total dissolved solids (TDS) using activated carbon media of palm shells, coconut shells, sawdust, and rice husks on water quality based on Minister of Health Regulation No.492 of 2010. The method used is the filtration method with a simple filtration device with a diameter of 4 inches and a length of 80 cm, and the thickness of each activated carbon is 30 cm and the filtration process with three filtration times, namely 2 hours, 4 hours, and 6 hours. The results showed that the four variations of activated carbon were proven to be able to improve water quality. The best-activated carbon in improving water quality from the turbidity parameter is sawdust activated carbon with a decreasing percentage of 75.09%, for pH and TDS parameters, namely rice husk activated carbon with a pH of 14.45%, and a TDS of 73.35 %. In conclusion, from the four variations of activated carbon, the best in improving water quality is the turbidity parameter, namely sawdust activated carbon, for the pH parameter, namely rice husk activated carbon, for the TDS parameter, coconut shell activated carbon.Keywords: Activated Carbon, Turbidity, pH, Total Dissolved Solids